Development and research trends of a polypropylene material in electrical engineering: A bibliometric mapping analysis and systematical review - Duan, Yubing; Zhao, Yonggui; Ma, Guoqing; Sun, Xiaobin; Zhang, Hao; Liu, Wenbo (Frontiers in Energy Research, 2023)
In order to explore the development and research trends of PolyPropylene (PP) in electric engineering, the research literatures are quantitatively analyzed by a bibliometric method with the VOSviewer and CiteSpace software. Firstly, the research literatures about PP material in the application of electric engineering are collected from 1990 to 2022. Then by analyzing the keyword co-occurrence, keyword co-occurrence timezone, author cooperation network and national cooperation network, the research hotspots of PP field as well as its time evolutionary path and development direction are introduced. It is found that the nano-modification, mechanical and electrical properties are the most popular research hotspots in this field. Most research were finished by a few specific researchers. A stable cooperative group has not formed in this field yet, indicating the necessity of further integration. Most articles about PP were published in the dielectric and material journals. It is suggested that more open access journals are required to popularize the existing research results to the public and to promote the development of PP. Although the most published country is China, the U.S. publishes the most cited papers on average.